Description of Imasaheleensis, gen. nov., sp. nov. (Imasidae, fam. nov.), a Deep‐Branching Marine Malawimonad and Possible Key Taxon in Understanding Early Eukaryotic Evolution. (19th January 2021) - Heiss, Aaron A.; Warring, Sally D.; Lukacs, Kaleigh; Favate, John; Yang, Ashley; Gyaltshen, Yangtsho; Filardi, Christopher; Simpson, Alastair G.B.; Kim, Eunsoo
Abstract: Malawimonadida is a deep‐level (arguably "kingdom‐scale") lineage of eukaryotes whose phylogenetic affinities are uncertain but of great evolutionary interest, as the group is suspected to branch close to the root of the tree of eukaryotes. Part of the difficulty in placing Malawimonadida phylogenetically is its tiny circumscription: at present, it comprises only two described and one cultured but undescribed species, all of them are freshwater suspension‐feeding nanoflagellates. In this study, we cultivated and characterised Imasa heleensis gen. nov., sp. nov. (Imasidae fam. nov.), the first marine malawimonad to be described. Light and electron microscopy observations show that Imasa is largely similar to other malawimonads, but more frequently adheres to the substrate, often by means of a pliable posterior extension. Phylogenetic analyses based on two ribosomal RNA genes and four translated protein‐coding genes using three different taxon sets place Imasa as sister to the three freshwater malawimonad strains with strong support. Imasa 's mitochondrial genome is circular‐mapping and shows a similar gene complement to other known malawimonads. We conclude that Imasa represents an important expansion of the range of taxa available for future evolutionary study.